Breeding of a thermostable xylanase-producing strain of Myceliophthora thermophila by atmospheric room temperature plasma (ARTP) mutagenesis - Zhang, Ning; Jiang, Yue; Sun, Yun-Juan; Jiang, Jian-Chun; Tong, Ya-Juan (Frontiers in Bioengineering and Biotechnology, 2023)
Hemicellulose is an important component in lignocellulose materials, which is second only to cellulose, accounting for 15%~35% of the dry weight of plants. In the current situation of energy shortage, making full use of lignocellulose materials to produce fuel ethanol has become an important way to solve the energy problem. Xylanase plays a crucial role in the utilization of hemicellulose. It is a necessary means to reduce the cost of hemicellulose utilization by improving the activity of xylanase. Moreover, most naturally xylanases are mesophilic enzymes, which limits their industrial application. In this study, Myceliophthora thermophila was used to produce xylanases and a thermostable mutant M 2103 was obtained by atmospheric room temperature plasma (ARTP) mutagenesis. The research work started with exploring the effects of ARTP mutagenesis on the antioxidase system (superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), polyphenol oxidase (PPO), and antioxidant capacity (AOC)) of M. thermophile, and found that SOD activity increased by 221.13%, and PPO activity increased by 486.04% as compared with the original strain when the implantation time was 300 s. So as to determine the conditions for subsequent mutagenesis. For the mutant M 2103, the reaction temperature for xylanase production remained stable in the range of 70 ℃-85 ℃. Its optimum temperature was 75 °C, which was 15 °C higher than that of the original strain. And its xylanase activity increased by 21.71% as compared with the original strain. M 2103 displayed a significantly higher relative xylanase activity than the original strain in the acidic (pH 4.0 − 7.0) range, and the xylanase activity was relatively stable in the pH range of 6.0 − 8.5. These results provide an alternative biocatalyst for the production of xylooligosaccharide, and a potential usage of ARTP in the mutagenesis of thermostable mutant.